Reconstruction of Late Quaternary Climate From a Paleo-Lacustrine Profile in the Central (Kumaun) Himalaya: Viewing the Results in a Regional Context - Sanwal, Jaishri; Rajendran, C. P.; Sheshshayee, M. S. (Frontiers in Earth Science, 2019)
In this paper, we reconstruct the climatic changes starting from late Pleistocene to the early Holocene as recorded from a fluvio-lacustrine section located within the Kumaun Central Himalaya. The results suggest two major climatic events corresponding with the Last Glacial Maximum (LGM) and Older Dryas (OD). The values of carbon isotopes vary between -23‰ to -14‰, along with a shift in vegetation pattern. The lower part of the section shows prevalence of C3 type vegetation, indicating warm and moist conditions at around 25,000 yr BP, possibly coinciding with the intensification of the Indian Summer Monsoon. The onset of cold and arid phase is evident in the gradual shift in vegetation pattern from C3 to C4 plants, which is prominently observed in the middle part of the paleolake profile. Eventually, as the value of δ13C during this time interval confirms, a prolonged phase of cold and arid climate sets in, coinciding with the strengthening of winter westerlies. This cold phase is dated at ~19,000 yr BP and the extended phase of cold interval observed at Dwarahat profile correlates well with previous results elsewhere from the Himalaya. The profile also shows that the LGM phase gradually transforms into a warm and moist climate. This transition registered at 200 cm above the base of the profile, marks the end of glacial period. The short, yet a clear warm spike could be related to the oscillation of Bølling-Allerød interstadial at ~15,000 yr BP. A significant negative excursion marked by an abrupt increase in δ13C values from -20‰ to -14‰ observed towards the top part of the profile, however, is reflective of the reduced monsoon precipitation, corresponding possibly with Older Dryas (OD). The topmost part of the profile that registers a depleted trend in δ13C values with dominance of C3 vegetation marks the return of the warm and moist climate.